Return-Entry Risk Communication Challenges: Experiences of Local Emergency Management Organizations following Superstorm Sandy. Issue 2 (August 2018) - Manandhar, Rejina; Siebeneck, Laura K.
The communication of risk and return-entry information is vital following a disaster. Although several studies examine challenges households experience when gathering information after an event, very little has been done to understand the communication challenges local emergency managers face during this time period. This study examines the risk communication challenges experienced by the local emergency management organizations in New Jersey after Superstorm Sandy (2012). Semi-structured telephone interviews were conducted with 25 local emergency management officials from the state of New Jersey. Qualitative data analysis using a grounded theory approach yielded four primary themes related to challenges: information challenges, technological challenges, organizational constraints, and social challenges. This article examines these four themes from the perspective of the local emergency manager and provides insights into the unique challenges these organizations faced in the aftermath of this disaster.